DESIGNING AND BUILDING A LEARNING MEDIA FOR EN-ROUTE FLIGHT INFORMATION - Aurina, Christy; Rochmawati, Laila; Akbar Awal Rozaq, Hasri; Putra, Iwansyah; Ratna Sari, Dewi (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
En-route Flight Information (EFI) is a science that studies the procedures for guiding aircraft in uncontrolled airspace. With the development of teaching aid technology, digitizing the EFI learning system in the form of a website-based TopSky Simulator is expected to make it easier for cadets to understand the concept of EFI learning about providing advisory and surveillance services in Uncontrolled Airspace. The deepening of EFI learning material is very necessary as a preparation for cadets before carrying out On the Job Training which must be undertaken by cadets of the Surabaya Aviation Polytechnic to carry out field work practices as an application of knowledge, especially in fields that have been studied during class education both in theory and practice. Therefore, the author intends to develop learning support facilities, especially the En-route Flight Information course by making this TopSky Simulator website. It is hoped that the information system and the features available in it can help teachers and cadets in learning flight traffic control via radar and practicing it well in the field